Durability analysis of reinforced concrete with loading induced cracks - Costa Junior, Milton Paulino; Moraes Pinheiro, Sayonara Maria (Revista ALCONPAT, 2021)
The objective of this study is to verify the relationship between the action of loads inducing cracks and the durability of reinforced concrete. Prismatic specimens were produced and for two years these samples were subjected to artificial salt spray, under the action of different types of loading and unloaded (reference), with moist curing for 7 days. Chloride penetration tests and microstructural analysis were carried out. It was observed that loading did not influence the results of chloride penetration. However, it was observed that in the micrographs and microanalysis of the cracked samples the clearer formation of deterioration products and possible microorganisms, compared to the samples that did not suffer loading.